FT-IR Analysis of Beta vulgaris Peels and Pomace Dye Extracts and Surface Analysis of Optimally Dyed-Mordanted Cellulosic Fabrics - Vincent Rotich; Phanice Wangila; Jackson Cherutoi (Journal of Chemistry)
FT-IR spectroscopy is a nondestructive technique that can be utilized for the qualitative characterization of natural dyes and dyed substrates through structure elucidation. This work aimed at the characterization of natural dye extract from Beta vulgaris peels and pomaces and surface analysis of optimally dyed-mordanted cotton (cellulosic) fabric using Fourier Transform Infrared (FT-IR) spectroscopy, as well as colour fastness tests (light, washing, rubbing, and perspiration). Response surface methodology (RSM) was employed in the optimization of dyeing temperature (T), time (t), and pH, as well as applying the relative percent change in colour strength (ΔE) of dyed fabrics as the response. The natural mordants (tannic acid-alum) were compared with synthetic mordants (K2Cr2O7, FeSO4, and CuSO4) using the three mordanting methods. The optimized dyeing parameters were T (55°C), t (75 minutes), and pH (6.5), as a result of comparatively high relative % ΔE (11%). The FT-IR analysis of the extract revealed different characteristic absorption peak values for various functional groups: 3282.82 cm−1 (–OH stretch), 2932.96 cm−1 (C–H stretch), and 1588.91 cm−1 (C=N stretch), among others. The C=N bond stretch biomarks the presence of nitrogen-containing compounds such as the reddish betanin pigments. p>0.05 of the dyeing parameters implied that they are not significant but affect dyeing probably alongside other factors such as mordanting. The spectral analysis of bleached and optimally dyed (nonmordanted and mordanted) fabrics revealed varied peaks indicating different functional groups suggesting the presence of cellulose and the binding of mordants with chromophores in the dye extract which yield different shades. Postmordanting showed mean ratings of 4-5 (excellent) among all fastness tests, displayed by tannic acid-alum, FeSO4, and CuSO4. Generally, mordanting resulted in enhanced dye stability and improved colour fastness. To identify specific chromophores in dye extracts and their molecular configurations due to mordants, advanced FT-IR hyphenated systems can be employed.